Aspek Hukum Dan Penyelesaian Sengketa Perjanjian Arisan Online Melalui Media Sosial Di Negeri Rumahkay Kecamatan Amalatu Kabupaten Seram Bagian Barat - Nabila, Syadzwina Hindun; Panjaitan, Wijaya Natalia; Labetubun, Muchtar Anshary Hamid (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Societies and online social media have evolved into new structures that play an important role in the lives of communities, nations, and nations. The new world structure that we're experiencing is developing very fast. A lot of people are not ready to face this new world. Special rules are also needed because online media makes it easier for humans. One of the new things is about the Arisan Agreement. Arisan is currently online. There are a number of gaps where online arisan participants can break the agreement. For example, they can leave the estate without paying a fine, pay a monthly fee after receiving the share, or tell others about the exit.Purposes of Devotion: To provide understanding and knowledge to the public especially in providing knowledge of legal aspects and dispute resolution of arisan agreements online through social media. Method of Devotion: The Service Method used is a method of counseling and mentoring the Rumahkay Community, especially in providing knowledge of legal aspects and resolving disputes over online arisan agreements through social media.Results of the Devotion: Arisan conducted online meets the legal requirements stipulated in Article 1320 of the Civil Code and is a form of legal agreement. The parties to the online arisan are valid in accordance with Article 1338 of the Civil Code after the agreement is valid. Where the online arisan agreement that has been agreed by the parties functions as a law. Where the agreed online arisan agreement applies like a law for the parties. So that if one of the pihal is negligent and cannot fulfill the achievement or perform his obligations, then the party can be said to have committed an act of default.